1994
DOI: 10.1093/nar/22.7.1226
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of the chicken erythroid δ-aminolevulinate synthase gene

Abstract: Erythroid cells regulate heme biosynthesis in a manner that is distinct from all other cell types. While heme negatively regulates the synthesis of the housekeeping delta-aminolevulinate synthase (ALAS-N) in all non-erythroid cells, the expression of an erythroid-specific isozyme (ALAS-E) is developmentally regulated in red blood cells. As a first step towards understanding the molecular basis for the transcriptional regulation of ALAS-E during erythropoiesis, we cloned and characterized the chicken ALAS-E loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Binding sites for GATA-1, NF-E2, and CACCC box-binding proteins have also been identified in the human ferrochelatase promoter (72). In contrast, the chicken ALAS2 promoter contains multiple binding sites for Sp1 (12). These studies, together with the information on globin gene expression (19), confirm that there is likely to be only a small number of erythroid cell-specific factors that act in a combinatorial fashion to ensure the coordinated regulation of heme and globin synthesis during erythropoiesis.…”
Section: Discussionmentioning
confidence: 75%
“…Binding sites for GATA-1, NF-E2, and CACCC box-binding proteins have also been identified in the human ferrochelatase promoter (72). In contrast, the chicken ALAS2 promoter contains multiple binding sites for Sp1 (12). These studies, together with the information on globin gene expression (19), confirm that there is likely to be only a small number of erythroid cell-specific factors that act in a combinatorial fashion to ensure the coordinated regulation of heme and globin synthesis during erythropoiesis.…”
Section: Discussionmentioning
confidence: 75%
“…QT6 cells were transfected with the reporter and effector plasmids by the calcium phosphate precipitation method as previously described (60). The chicken erythroid cell line HD3 (5) was maintained and transfected by the DEAE-dextran method as previously described (41). Luciferase assays were performed by the luciferase assay system (Promega) by following the supplier's protocol and with a Biolumat luminometer (Berthold).…”
Section: Methodsmentioning
confidence: 99%
“…The first exon of the gene was identified to be a small discrete exon coding for a 5' UTR, and the gene consists of eleven exons which encompass about 14 kb in the rat genome. As shown in Figure 1, comparison of the structure and organization of the rat ALAS-N gene to those of chicken ALAS-N [31] and the chicken [33], mouse [25] and human [34] ALAS-E genes revealed that the organization of these genes is highly conserved. ALAS-N genes appeared to be organized more compactly than ALAS-E genes.…”
Section: Organization Of the Genes Encoding Alas-e And Alas-n Is Highmentioning
confidence: 99%
“…This observation suggested that the genes encoding ALAS-N and ALAS-E have diverged from a common ancestor, and the first exon in the chicken ALAS-N gene fused during molecular evolution. The structure of ALAS-E first exons is highly conserved among the chicken, human and mouse ALAS-E genes [15,33,35,361. When processed to m R N 4 the calculated free energy of the predicted stem-loop secondary structure formed by the first and a portion of the second exons of chicken ALAS-E is -16.8 kCal/mol, suggesting that this RNA structure may be of functional significance.…”
Section: Organization Of the Genes Encoding Alas-e And Alas-n Is Highmentioning
confidence: 99%